Trust to Contractor in Housing Construction - Chandra, H.P.; Limanto, S. (Institute of Research and Community Outreach - Petra Christian University, 2014)
Trust is the willingness to rely upon the actions of others, to be dependent upon them, and thus to be vulnerable to their actions. In housing construction, where contract is usually awarded without tender, trust of the developer to the contractor is a very important factor. This paper studies trust relationship, specifically on the developer’s side to contractor. Trust is measured by identifying three major factors: characteristics, how to build, and the benefits of trust. Fifteen respondents from fifteen housing developers in West Surabaya, Indonesia, participated in the questionnaire survey. The results indicated that characteristics of trust depend on the credibility of the contractor, which is the depth of its experience. Trust can be built by creating team compatibility and aligning issues; and behaving professionally. Trust can help the contractor accelerate in solving the problem in construction.